2006
DOI: 10.1111/j.1601-183x.2006.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of two P‐element enhancer‐trap insertion lines that show expression in the giant fibre neuron of Drosophila melanogaster

Abstract: The giant fibre system (GFS) of Drosophila is a simple neural circuit that mediates escape responses in adult flies. Here we report the initial characterization of two genes that are preferentially expressed in the GFS. Two P-element insertion lines, carrying the GAL4 transcriptional activator, were identified that exhibited pronounced expression in elements of the GFS and relatively low levels elsewhere within the adult central nervous system. Genomic DNA flanking the P-element insertion site was recovered fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…2B), whereas mutations that decrease behavioral bang-sensitivity raise the threshold [29], [42]. Examination of kcc RNAi-induced seizure-susceptibility showed that the threshold to evoked seizure-like discharges of experimental A307-GAL4 (driving in a subset of neurons [43], [44]) flies (genotype: A307-GAL4>kcc-RNAi-V ) was about one-fourth that of wild-type and control genotypes (Fig. 2C).…”
Section: Resultsmentioning
confidence: 95%
“…2B), whereas mutations that decrease behavioral bang-sensitivity raise the threshold [29], [42]. Examination of kcc RNAi-induced seizure-susceptibility showed that the threshold to evoked seizure-like discharges of experimental A307-GAL4 (driving in a subset of neurons [43], [44]) flies (genotype: A307-GAL4>kcc-RNAi-V ) was about one-fourth that of wild-type and control genotypes (Fig. 2C).…”
Section: Resultsmentioning
confidence: 95%
“…Flies also were tested for suppression using a307-GAL4, a line expressed strongly and specifically in the GF neurons (Allen et al 2007). While no behavioral effect was observed in the para bss1 /+ mutant flies, nor were seizure thresholds increased at room temperature, we saw strong suppression with a307-GAL4 in para bss1 and eas genotypes that were preincubated at 28°before bang testing ( Figure 7C).…”
Section: Electrophysiological Deficits In Shi Ts1 Mutants Indicate Symentioning
confidence: 99%
“…We used electrophysiology to assay GFS function, which, in combination with morphological analysis, can reveal abnormalities of synaptogenesis during development [4-7,9,11,12,20]. A severe GF-TTMn synaptic phenotype is caused by over-expression of Gl DN ; some flies fail to respond to brain stimulation and those that do respond exhibit a long response latency and show only a single response or poor following to repetitive stimuli ([20]; Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies using over-expression of dominant-negative transgenes, or homozygous adult viable mutations, have recently shed light on signaling mechanisms during the formation of the GF-TTMn synapse. These include the receptors Semaphorin 1a and Roundabout [4,5]; the L-1 type cell-adhesion molecule Neuroglian [6]; the endocytotic and ubiquitin machinery [7-10]; the small GTPase DRac1 [11], and the transcription factor Ken [12]. However, the precise mechanisms by which these integrate during synaptogenesis are yet to emerge.…”
Section: Introductionmentioning
confidence: 99%